CURRICULUM RECONSTRUCTION FOR AI-BASED ISLAMIC RELIGIOUS EDUCATION IN THE SOCIETY 5.0 ERA AT MADRASAH - Mukhsin Mukhsin; Ade Zaenul Mutaqin; Muhammad Hijrah M Saway; Kiki Kiki; Abdul Hamid (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aims to address the urgency of reconstructing the Islamic Religious Education (IRE) curriculum based on Artificial Intelligence (AI) and aims to develop a comprehensive framework that aligns with the digital needs of students in the era of Society 5.0. This study uses a qualitative approach with a case study type involving 19 informants consisting of IRE teachers, students, Deputy Heads of Curriculum, and Madrasah Principals. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using the Braun and Clarke thematic analysis framework with validation through triangulation and member checking. The results of the study indicate that the previous IRE curriculum, which focused on memorization and teacher-centered teaching, created a significant gap between students' cognitive knowledge and their ability to apply Islamic values in a digital context. The proposed AI-based curriculum reconstruction includes three interrelated components: Basic Analysis (evaluating the previous curriculum gaps and AI resource needs), Pedagogical Transformation (redesigning methods through a blended learning model), and Systemic Integration (AI-based implementation strategies and evaluation systems). Ongoing challenges include teachers' limited AI competency, inadequate infrastructure, and ethical concerns regarding the preservation of Islamic values. This model offers a scalable blueprint for madrasas navigating digital transformation while preserving the spiritual essence of Islamic education in the era of Society 5.0.